A Review of Citizen Participation Issues, Responses, and Prospects for Reform in Local Development Councils - Medina-Guce, Czarina; Galindes, Ana Martha (Philippine Journal of Public Administration, 2019)
This article conducts a review of citizen participation in local governance within the context of the local development councils (LDCs). It argues that the Local Government Code has prescribed citizen participation with a limited set of standards, namely, the 25% civil society membership in the LDC and the administrative indicators of activities that the LDC must perform. The Code and subsequent LGU performance measures it influenced have insufficiently addressed the roles to play and capacities needed by civil society to realize higher levels of citizen participation in the LDCs. Moving forward, the study takes stock of citizen participation initiatives that make explicit the roles and capacities of civil society organizations in local decision making and draws lessons to suggest prospects for deepening and increasing citizen participation in LDCs. The article ends with a note that citizen participation should be in the core agenda of proposed amendments in the Code.
Keywords: local development council, local government units, citizen participation